Representações em disputa: trabalhismo e PTB nas páginas dos jornais cariocas Ultima Hora e Correio da Manhã (1951-1954) - Souza, Pâmela Chiorotti Becker (2021)
This research investigates how the trabalhismo (labourism) and Partido Trabalhista Brasileiro (PTB) were represented on the pages of the newspapers Correio da Manhã and Ultima Hora from Rio de Janeiro during the second Vargas' government, considering these publications as representation instruments engaged on a symbolic struggle for the most legitimate definition of the analysed objects. For such aim, the intention is to join these analysis to the understanding of the textual materials as part of a specific conjuncture, evaluating if the construction of the representation by both newspapers move closer or further away from each other over time. Another aim, wider, is to reevaluate the possibility of using, at least in relation to Correio da Manhã and Ultima Hora, the traditional affirmation from the historical studies linked to the press about the newspapers subjection to the political and financial groups that they were associated. Accordingly, this work justification is on the absence of studies of such kind, the comparison of two newspapers of different positions, that make a wider research of their views on two elements, PTB and trabalhismo (labourism). The methodology was inspired on the Content Analysis through Bardin's (2004) and Moraes' (1998) works because such tool allows the organization of the categories drawn from the documentary corpus, connecting them to the particular historical context of the historiographical research. The results point to a relative autonomy of the publications regarding the inclination of their symbolic construction, differently from what is expected when the way that these newspapers were presented in history in recent years is considered. Moment in which new studies started a renovation of the view on the journalistic universe of the 1950s.